2009
DOI: 10.17221/260-pse
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of leaf hydraulics in sunflower (Helianthus annuus L.) under drought stress

Abstract: Improvement in leaf hydraulics is directly related to the improvement of plant tolerance to drought stress. Therefore, a field and pot experiment was carried out to determine the type of genetic variability and selection of parental types on the basis of combining ability for leaf hydraulics. Genotypes showed similar performance in both experiments; higher values were shown by drought tolerant genotypes in all traits except for osmotic potential, which drought tolerant genotypes maintained lower. Osmotic adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…However, contrary to this, varieties BOU-1724, FH-1000, NF-801 and 4F were found susceptible. Rauf et al (2009) viewed that osmotic adjustment is increased with the increase in root length, and thus plants showed more tolerance under water deficit conditions therefore, during the present investigation longer root length of tolerant varieties might be due to higher osmotic adjustment and retention of more water content in plants, suggesting that root growth is a reliable indicator for moisture stress tolerance in crops (Gesimba et al, 2004). The data generated by some previous workers substantiate our results (Malik et al, 2006;Ullah et al, 2008;Ahmad et al, 2009;Iqbal et al, 2011), which make the present technique reliable and efficient for any drought screening program.…”
Section: Discussionmentioning
confidence: 58%
“…However, contrary to this, varieties BOU-1724, FH-1000, NF-801 and 4F were found susceptible. Rauf et al (2009) viewed that osmotic adjustment is increased with the increase in root length, and thus plants showed more tolerance under water deficit conditions therefore, during the present investigation longer root length of tolerant varieties might be due to higher osmotic adjustment and retention of more water content in plants, suggesting that root growth is a reliable indicator for moisture stress tolerance in crops (Gesimba et al, 2004). The data generated by some previous workers substantiate our results (Malik et al, 2006;Ullah et al, 2008;Ahmad et al, 2009;Iqbal et al, 2011), which make the present technique reliable and efficient for any drought screening program.…”
Section: Discussionmentioning
confidence: 58%
“…However, contrasting reports are available showing the usefulness of specific classes of traits under abiotic stress (Rauf & Sadaqat 2008a, 2008bRauf et al 2012). Greater progress in yield improvement and resistance can be made by exploiting traits associated with heat resistance under a stress environment Rauf 2008;Rauf et al 2009Rauf et al , 2012). An ideal screening trait may successfully be able to discriminate resistant from susceptible types, and may be measured rapidly, well before the onset of the reproductive stage, thus there is a possibility of teasing out undesirable plants before reaching reproductive maturity (Rauf 2008) while the magnitude of variation for the traits may be high in a population, and should show a positive relationship with yield, thus productive, heat-resistant genotypes may be selected in segregating generations.…”
Section: Genetics Of Heat Resistancementioning
confidence: 99%
“…However, sustainability of this high-yield potential will depend on the hybrids or population stability and resistance to biotic and abiotic stresses. The achene yield of sunflower is threatened by various biotic and abiotic factors (Rauf 2008;Rauf et al 2009Rauf et al , 2012. These factors may dictate the yield potential of sunflower by repressing those traits contributing to high achene yield in sunflower.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown genetic variation among sunflower genotypes for tolerance to abiotic stress such as drought, salinity and heat stress (Kalyar et al, 2013;Rauf, 2008;Rauf and Sadaqat, 2008;Rauf et al, 2009Rauf et al, , 2012. Despite heat stress being an important yield limiting factor (Chimenti and Hall, 2001;Ploschuk et al, 1995;Rondanini et al, 2003Rondanini et al, , 2006, little efforts have been carried out to study the responses of sunflower to heat stress and to introgress heat resistance in sunflower germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this trait was a non-destructive type, and could be measured easily, rapidly and at a low cost. Rauf et al (2009) also indicated that the usefulness of traits could be indicated Table 6 Mean values for the leaf gas exchange traits photosynthetic photon flux density (PPFD), leaf temperature (T leaf ), net photosynthesis rate (PN), stomatal conductance (gs) and transpiration rate (E) in upward and downward inclined leaves under heat stress in F2 population derived from CM207 × CM631. from the magnitude of genetic variability, which is an easy and cost-free measurement.…”
Section: Discussionmentioning
confidence: 99%